Development of a coupling between a system thermal–hydraulic code and a reduced order CFD model. (April 2021) - Star, S. Kelbij; Spina, Giuseppe; Belloni, Francesco; Degroote, Joris
Highlights: Coupling between RELAP5-MOD3.3 and a reduced order model of the CFD solver Open-FOAM. The coupled model is 3–5 times faster than coupling RELAP5 with the CFD solver. The coupled simulation results are close to those of coupled RELAP5/CFD simulations. Methodology works well on open and closed pipe flow configurations. Tested and evaluated the coupled model on parametric problems. Abstract: The nuclear community has coupled several three-dimensional Computational Fluid Dynamics (CFD) solvers with one-dimensional system thermal–hydraulic (STH) codes. This work proposes to replace the CFD solver by a reduced order model (ROM) to reduce the computational cost. The system code RELAP5-MOD3.3 and a ROM of the finite volume CFD solver OpenFOAM are coupled by a partitioned domain decomposition coupling algorithm using an implicit coupling scheme. The velocity transported over a coupling boundary interface is imposed in the ROM using a penalty method. The coupled models are evaluated on open and closed pipe flow configurations. The results of the coupled simulations with the ROM are close to those with the CFD solver. Also for new parameter sets, the coupled RELAP5/ROM models are capable of predicting the coupled RELAP5/CFD results with good accuracy. Finally, coupling with the ROM is 3–5 times faster than coupling with the CFD solver.